Improving Mobile GIS applications through the identification of Geographic Context - Seabra, Guilherme Jorge Birra (2021)
Mobile devices are becoming increasingly popular. Their functionalities have become more than just making phone calls, due to regular improvements to these devices. Thus, with their notable increase in computational power, these devices have become able to support applications based on georeferenced data. By allowing the manipulation, visualisation and sharing of such data, these applications (supported by, for example, Google Maps or OpenStreetMap) have also shown an increasingly higher popularity. In this dissertation, we developed an adaptive Geographic Information System for Android devices, which displays relevant information to the user, based on the detected geographic context. The platform is supported by the concept of a context adaptation model, which enables the identification of particular situations in the context of the user, and the consequent adaptation of the application’s interface to the identified event. The context of the user is composed of the information collected by the sensors present in most mobile devices, which also enables the system to automatically adapt its content and thus become more relevant (according to the detected conditions), contributing for a better user experience. The relevant events to be listened to and the actions to be taken accordingly are managed in an administrator online tool, allowing for simplified software maintenance. By defining adaptation rules on aWeb platform, the administrators are able to configure the Android application’s behaviour without having to change the existing code. Finally, the developed platform was tested on a prototype of a Tourism application. The system was evaluated in two distinct parts - Web platform and Android application - by several participants, who agreed that the second is easy to use, while the first requires some previous learning.